A Research-Based Summary on Trace Minerals for Cattle - João H. Jabur Bittar; Roberto A. Palomares (EDIS)
Producers can utilize mineral supplementation to improve cattle production and herd health, which has the potential to reduce antibiotic usage. This publication presents a summary on trace minerals for cattle. Written by João H. Jabur Bittar and Roberto A. Palomares, and published by the UF/IFAS Veterinary Medicine—Large Animal Clinical Sciences Department, October 2021.